A snapshot of Physical Education in Italian primary schools: assessing the resources available for an instrument of health promotion - Valeriani, Federica; Masini, Alice; Baldelli, Giulia; Dallolio, Laura; Eid, Luca; Lovecchio, Nicola; Stefanizzi, Pasquale; Ursino, Simona; Gallè, Francesca (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Regular physical activity is crucial in preventing chronic diseases. International health authorities recommend that children and adolescents engage in at least 60 minutes of moderate to vigorous physical activity per day to achieve health benefits. Offering regular exercise opportunities to young people can promote the development of healthy lifestyles. In 2021, a new regulation introduced up to two compulsory hours of Physical Education per week in Italy and established that Physical Education should be entrusted to adequately trained teachers. The present study aimed to assess, from the perspective of the new teachers, the resources available for Physical Education in Italian primary schools.Methods. A questionnaire-based cross-sectional study was conducted among primary school Physical Education teachers during the year 2022-2023. Their opinion about the school resources were analyzed in light of their demographic characteristics and work experience.Results. Out of the 118 participating teachers, 96 (81.3%) reported the presence of a gym in their school. Participants expressed satisfaction with the size and windows of the gym, particularly for the schools of the North, as well as the adequacy of outdoor spaces. However, lower levels of satisfaction for locker rooms and gym small equipment emerged, especially among those teachers with less work experience.Conclusions. The introduction of the Physical Education teacher figure in Italian primary schools was an important step for health promotion in our country. However, some aspects related to the structural resources should be considered in future policies.